2019
DOI: 10.1186/s13018-019-1450-0
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of nano-hydroxyapatite/poly(vinyl alcohol) hydrogels coated with poly(lactic-co-glycolic acid)/nano-hydroxyapatite/poly(vinyl alcohol) scaffolds for cartilage repair

Abstract: BackgroundPoly(vinyl alcohol) (PVA) hydrogels have been widely used in synthetic cartilage materials. However, limitations of PVA hydrogels such as poor biomechanics and limited cell ingrowth remain challenges in this field.MethodsThis work aimed to design novel nano-hydroxyapatite (nano-HA)/poly(vinyl alcohol) (PVA) hydrogels coated with a poly(lactic-co-glycolic acid) (PLGA)/nano-HA/PVA scaffold to counter the limitations of PVA hydrogels. The core, comprising nano-HA/PVA hydrogel, had the primary role of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…At the same time, the degradation process of nHA does not produce harmful substances. Proposed composite hydrogels with nHA for the repair of cartilage defects in rabbits, and they found that composite hydrogels had elevated mechanical properties, and were conducive to the adhesion and proliferation of seeded rabbit chondrocytes, with promising potential for the repair of cartilage defects Su et al (2019) . Zhu and coworkers adopted nHA and polylactic acid to prepare cartilage scaffolds and used BMSCs as progenitor cells to repair rabbit full-thickness cartilage defects, the histological and immunohistochemical analyses showed that the cartilage defect was effectively repaired with a large amount of extracellular matrix produced Zhu et al (2017) .…”
Section: Nanoparticles Applied In Cartilage Regenerationmentioning
confidence: 99%
“…At the same time, the degradation process of nHA does not produce harmful substances. Proposed composite hydrogels with nHA for the repair of cartilage defects in rabbits, and they found that composite hydrogels had elevated mechanical properties, and were conducive to the adhesion and proliferation of seeded rabbit chondrocytes, with promising potential for the repair of cartilage defects Su et al (2019) . Zhu and coworkers adopted nHA and polylactic acid to prepare cartilage scaffolds and used BMSCs as progenitor cells to repair rabbit full-thickness cartilage defects, the histological and immunohistochemical analyses showed that the cartilage defect was effectively repaired with a large amount of extracellular matrix produced Zhu et al (2017) .…”
Section: Nanoparticles Applied In Cartilage Regenerationmentioning
confidence: 99%
“…The composite hydrogel provides better compressive strength and enhanced biocompatibility compared to the PVA hydrogels. Additionally, in vitro studies were carried on rabbits by implanting rabbit chondrocytes in the composite hydrogel and the better composition was found to be 30 wt % poly­(lactic- co -glycolic acid), 5 wt % HAP, and 15 wt % PVA, which shows enhanced mechanical properties, cell adhesion, and cellular proliferation …”
Section: Miscellaneous Tissue Engineering Applicationsmentioning
confidence: 99%
“…Usually inorganic materials that are silicon‐based (e.g., methyl dimethoxy silane, [ 32 ] methacrylate‐functionalized silica nanoparticle (MSi), [ 65 ] bioactive glass (BG) [ 30 ] ), carbon‐based (e.g., graphene oxide, [ 75 ] hydroxyapatite (HA) [ 31,80 ] ), and metal oxide‐based. [ 68,81 ] These nanocomposites can be divided into nanoparticles, nanofibers, nanosheets, and nanotubes according to their different shapes.…”
Section: Strengthening Mechanisms and Basic Property Characterizationmentioning
confidence: 99%
“…Su et al. [ 80 ] prepared a double‐layer hydrogel by two‐step molding method, whose coating is poly(lactic‐ co ‐glycolic acid) (PLGA)/nano‐HA/PVA scaffold and the core is HA/PVA hydrogel. Meng et al.…”
Section: Functional Modifications Of Pva Hydrogelsmentioning
confidence: 99%